Advances in treatment of elderly primary central nervous system lymphoma. (26th August 2021) - Martinez‐Calle, Nicolas; Isbell, Lisa K.; Cwynarski, Kate; Schorb, Elisabeth
Summary: The management of older individuals (≥60 years) with primary central nervous system lymphoma remains a clinical challenge. Identification of optimal therapy and delivering adequate dose intensity are two of the major issues in treating elderly patients. Premorbid performance status and comorbidities influence individualised treatment approaches and geriatric assessment tools are increasingly utilised. Optimal induction treatment remains high‐dose methotrexate‐based immunochemotherapy, delivery is feasible in the majority of patients and the goal of treatment remains achieving complete remission. Consolidation strategies are also relevant in the elderly, aiming to maximise duration of response and quality of life (QoL). Potential options include high‐dose therapy with haematopoietic stem cell consolidation, non‐myeloablative chemotherapy and whole‐brain radiotherapy. Efficacy of novel agents, such as Bruton tyrosine kinase inhibitors and lenalidomide, have been reported; these represent an alternative for elderly patients unfit for chemotherapy. Prognosis remains poor, improvement of outcomes in this age group is urgently needed.